Determining Profitable Annual Forage Rotations - J. D. Holman; T. Roberts; S. Maxwell; I. Kisekka (Kansas Agricultural Experiment Station Research Reports, 2016)
Producers are interested in growing annual forages, yet the region lacks proven recommended crop rotations such as those for grain crops. Forage production is important to the region’s livestock and dairy industries and is becoming increasingly important as irrigation well capacity declines. Forages require less water than grain crops and may allow for increased cropping intensity and opportunistic cropping. A study was initiated in 2013 comparing several 1-, 3-, and 4-year forage rotations with no-till and minimum-till (min-till). Data presented are from 2013 through 2015. Winter triticale yields were increased by tillage. Double-crop forage sorghum yielded 23% less than full-season forage sorghum across years. Oats failed to make a crop in 2013 and do not appear to be as drought tolerant as spring triticale or forage sorghum. Subsequent years will be used to compare forage rotations and profitability.
Keywords: annual forage rotations; profitable forage; annual forages; winter triticale; double crop forage sorghum; spring oat; triticale; forage sorghum